2017
DOI: 10.1136/emermed-2016-206467
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol identification and intervention in English emergency departments

Abstract: Alcohol screening together with referral or intervention is becoming part of routine practice in England. Compared with our previous national survey, increases in alcohol screening and intervention activity are demonstrated, with improvements in routine questioning (among adults), the number of general practitioners being informed about alcohol-related attendances, provision of training, access to specialist services and the use of formal screening tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The National Institute on Alcohol Abuse and Alcoholism has proposed several clinical situations as key opportunities to screen for at-risk drinking, including in emergency departments or urgent care centers, and when prescribing a medication that interacts with alcohol [ 3 ]. The emergency department is an important clinical setting for screening for at-risk drinking and conducting brief interventions, and many studies have shown that brief interventions in the emergency department focusing on alcohol consumption are effective [ 4 - 7 ]. However, it is often difficult to administer the full AUDIT questionnaire, which consists of 10 questions, in the emergency department, where urgent care is conducted simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The National Institute on Alcohol Abuse and Alcoholism has proposed several clinical situations as key opportunities to screen for at-risk drinking, including in emergency departments or urgent care centers, and when prescribing a medication that interacts with alcohol [ 3 ]. The emergency department is an important clinical setting for screening for at-risk drinking and conducting brief interventions, and many studies have shown that brief interventions in the emergency department focusing on alcohol consumption are effective [ 4 - 7 ]. However, it is often difficult to administer the full AUDIT questionnaire, which consists of 10 questions, in the emergency department, where urgent care is conducted simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 The emergency department is an important clinical environments for screening at-risk drinking and conducting brief interventions, and many studies have shown that brief interventions in the emergency department focused on alcohol consumption are effective. 8 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…The study by Patton and Green in this month’s issue6 is encouraging. It is the third survey in a series, to determine the level of alcohol ‘identification’ and the provision of brief advice in EDs in England.…”
mentioning
confidence: 78%